2008
DOI: 10.1017/s0142716408080223
|View full text |Cite
|
Sign up to set email alerts
|

Integrating articulatory constraints into models of second language phonological acquisition

Abstract: Models such as Eckman's markedness differential hypothesis, Flege's speech learning model, and Brown's feature-based theory of perception seek to explain and predict the relative difficulty second language (L2) learners face when acquiring new or similar sounds. In this paper, we test their predictive adequacy as concerns native English speakers' mastery of French /Â/ and Spanish /|/. Based on an acoustic analysis of the learner data, we demonstrate that these three models do not account for the full range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 55 publications
2
57
0
Order By: Relevance
“…The findings of the study (discussed in §4 and §5) support previous research (Colantoni & Steele 2008) that not only are perceptual factors at play during second language acquisition, but also general articulatory concerns. Continuing to define the roles of perception and articulation in L2 acquisition processes will help to develop more explanatory theories of L2 phonological acquisition.…”
Section: Introductionsupporting
confidence: 84%
“…The findings of the study (discussed in §4 and §5) support previous research (Colantoni & Steele 2008) that not only are perceptual factors at play during second language acquisition, but also general articulatory concerns. Continuing to define the roles of perception and articulation in L2 acquisition processes will help to develop more explanatory theories of L2 phonological acquisition.…”
Section: Introductionsupporting
confidence: 84%
“…Major 1986 andWaltmunson 2005), and taps in an onset cluster were produced later than intervocalic taps (e.g. Colantoni &Steele 2008, Major 1986 andWaltmunson Brought to you by | Nanyang Technological University Authenticated Download Date | 6/1/15 3:14 AM 2005). However, it remains to be seen how tap and trill production develops in these two environments.…”
Section: Resultsmentioning
confidence: 99%
“…Although special emphasis was put on the effects of Age of Learning (AOL), Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 5/27/15 3:43 PM they found that the accuracy with which L2 vowels were produced was limited by how accurately they were perceived. Other research studies on speech perception and/or production based on the hypotheses of the SLM include Aoyama et al (2004); Baker et al (2002); Chen and Fon (2007); Cheon (2007); Colantoni and Steele (2008); Ingvalson et al (2011);Evans (2007, 2009);Larson-Hall (2004); Mennen (1998); Segui and Halle (2001);and Pilus (2003). Regardless of the focuses of the studies and of whether the results categorically supported the SLM, it is evident that the similarity between the target and native languages has received increasing attention, and that speech perception is often intimately related to speech production.…”
Section: Research On the Speech Learning Modelmentioning
confidence: 99%